2005
DOI: 10.1038/sj.jcbfm.9600013
|View full text |Cite
|
Sign up to set email alerts
|

FK419, a Nonpeptide Platelet Glycoprotein IIb/IIIa Antagonist, Ameliorates Brain Infarction Associated with Thrombotic Focal Cerebral Ischemia in Monkeys: Comparison with Tissue Plasminogen Activator

Abstract: The binding of platelet glycoprotein (GP) IIb/IIIa to fibrinogen is the final common pathway in platelet aggregation, a process known to play a key role in the pathogenesis of ischemic brain damage. We compared the effects of FK419, a novel nonpeptide GPIIb/IIIa antagonist, with recombinant tissue plasminogen activator (rt-PA) on middle cerebral artery (MCA) patency and ischemic brain damage in a thrombotic stroke model in squirrel monkeys. FK419 not only inhibited in vitro platelet aggregation (IC 50 : 88 nmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…46 Several experimental studies reported a beneficial effect of GPIIb/IIIa antagonists on stroke size and functional outcome. 44,47,48 GPIIb/IIIa antagonists also have been successfully used in experimental and clinical settings in conjunction with recombinant tissue-type plasminogen activator thrombolysis therapy without major complications reported. 49,50 This is in contrast to our study in which no effect on stroke volume or functional deficit was observed, regardless of the anti-GPIIb/ IIIa F(ab) 2 dosage used.…”
Section: Discussionmentioning
confidence: 99%
“…46 Several experimental studies reported a beneficial effect of GPIIb/IIIa antagonists on stroke size and functional outcome. 44,47,48 GPIIb/IIIa antagonists also have been successfully used in experimental and clinical settings in conjunction with recombinant tissue-type plasminogen activator thrombolysis therapy without major complications reported. 49,50 This is in contrast to our study in which no effect on stroke volume or functional deficit was observed, regardless of the anti-GPIIb/ IIIa F(ab) 2 dosage used.…”
Section: Discussionmentioning
confidence: 99%
“…After administration of lower doses was found after staining with triphenyltetrazolium chloride, a significantly smaller infarct volume than expected [11]. Other studies in experimental stroke models in guinea pigs and squirrel monkeys with the non-peptide GPIIb/IIIa blocker FK419 could uncover no bleeding complications, but showed reduced infarct volume as an indication of their effectiveness [12,13].…”
Section: Discussionmentioning
confidence: 96%
“…Further evidence for this contention comes from the fact that baboons do not rub or pick at their exenterated orbit, show no favoritism to it and show no physiological evidence of pain such as increased blood pressure, heart or respiratory rate. Femoral vascular access sites are similarly ignored (Maeda et al 2005;Marshall et al 2003;Qureshi et al 2005).…”
Section: Experimental Primate Stroke-methods Mod-ifications and Impmentioning
confidence: 99%